Warrior women remaking postsecondary places through relational narrative inquiry - Young, Mary Isabelle; Joe, Lucy (Emerald, 2012)
Warrior Women makes visible the ongoing intergenerational narrative reverberations (Young, 2003; 2005) shaped through Canadas residential school era which denied the communal and cultural, economic, educational, human, familial, linguistic, and spiritual rights of Aboriginal people. Attending to these narrative reverberations foregrounded the continuing colonial barriers faced by six Aboriginal post secondary students as they composed their lives in a current era of increasing standardization in Canadian universities and schools. Yet, what also became visible were ways in which the Aboriginal teachers increasingly reclaimed or drew upon their ancestral ways of knowing and being. In this retelling and reliving of their stories to live by (Connelly & Clandinin, 1999) the teachers were composing counterstories (Lindemann Nelson, 1995). While they wakefully composed and lived out these counterstories with intentions of interrupting dominant social, cultural, and institutional narratives they were, at the same time, alongside children, youth, grandchildren, family members, community members, Elders, and colleagues with whom they interacted, co-composing new possible intergenerational narrative reverberations. These new possible intergenerational narrative reverberations carry significant potential to reshape the future life possibilities of Aboriginal and non-Aboriginal children, youth, families, and communities in Canada; they also carry significant potential to reshape the school and post secondary places experienced by future generations of Aboriginal and non-Aboriginal post secondary students.
Keywords: Education -- Higher.; Education -- General.; Higher & further education, tertiary education.; Educational: English literature.; Indigenous peoples -- Education (Continuing education) -- Canada.; Teachers -- Canada.; Off-reservation boarding schools -- Canada -- History.; Narrative inquiry (Research method) -- Case studies.; elektronické knihy; electronic books